Sistem Informasi Geografis Pemetaan Penyebaran Penyakit Demam Berdarah Di Kabupaten Kampar Berbasis Web (Analyst) - Yery, Aprian Musthofa; Azriadi, Emon; Gusman, Deddy (Journal on Pustaka Cendekia Informatika, 2023)
Dengue Hemorrhagic Fever (DHF) is a disease caused by dengue virus infection. DHF is an acute disease with clinical manifestations of bleeding that causes shock that ends in death. Dengue fever is caused by one of the four virus serotypes of the genus Flavivirus, family Flaviviridae. Almost every year an Extraordinary Event (KLB) occurs in several areas during the rainy season. This disease is still a public health problem and is endemic in several districts/cities in Indonesia. Dengue Hemorrhagic Fever (DHF) is still a public health problem in Kampar Regency which requires serious attention from various parties considering that this disease has the potential to cause an outbreak and is a threat to the wider community. Therefore it is necessary to have a web-based Geographic Information System for Mapping the Spread of DHF in Kampar District so that it can assist the Health Service and the community in handling DHF in Kampar District. The designed system is a web-based system as a medium for providing information to the public. In testing the system using the black box testing method.